Memória emocional de ratos selecionados no campo aberto em alto e baixo rearing: aquisição, consolidação e extinção no condicionamento de medo - Figueredo, Larissa Zeggio Perez [UNIFESP] (2010)
Rearing behavior displays a fundamental role in exploration, being considered more efficient in search and input of enviroment information than other exploratory behaviors. The hippocampal formation is the main neural structure involved in the interplay of rearing, cognitive map formation and emotion. Furthermore, selection of subgroups of animals displaying high or low rearing expression can enlarge the evaluation of potential correlated neurobiological differences. In the present work, the memory acquisition, consolidation, forgetting and extinction in the context and tone fear conditioning tasks (CFC and TFC, respectively) were investigated in animals displaying high and low rearing towards open field novelty exposure. The firts part shows that animals performance differs in some aspects of CFC, but not TFC. Animals from both HR and LR subgroups learn equally CFC and TFC tasks, when evaluated 24 hours after training. When the test session of the tasks is done 30 days after training, LR subgroup displays hyperconsolidation in comparison to HR subgroup only in CFC task. LR animals also take more time to extinguish CFC task than HR animals, while extinction is similar between groups in TFC. The behavioral pattern shown by LR animals seems analogous to traumatic memory hyperconsolidation, a behavioral symptom of post traumatic stress disorder (PTSD). To investigate this hypothesis, the second part of the present work evaluated the influence of the tricyclic antidepressant imipramine (20 mg/kg) and of the benzodiazepine diazepam (10 mg/kg), which are used in PTSD therapeutics, in the emotional memory extinction of CFC of animals from HR and LR subgroups, in the sense to diminish hyperconsolidation of LR animals. Results show that HR and LR animals which received imipramine or diazepam after session of extinction of CFC task did not show any significant difference when compared to their respective saline treated counterpart. The results are discussed in the sense to use animals from LR subgroup as pontential animal model of PTSD, and the limits of it.